A scalable resource allocation framework for SVC video transmissions over downlink MIMO-OFDM networks - Li, Maodong (2013)
In this paper, we propose a scalable resource allocation framework for transmission of multiple scalable videos over downlink MIMO-OFDM networks. First, we analyze the rate-utility relationship of scalable video by a packet prioritization scheme, which ensures an optimized video utility under the rate constraint. The scalable framework is then proposed to achieve differentiated service objectives for different video layers. To provide every user with a fair opportunity to receive video for basic viewing, a MAXMIN fairness is designed to have their base layer video packets received. When all users have their base layer packets successfully received, the resources are distributed to exploit network efficiency. Resource allocations are accomplished by the efficient bit loading and power allocation for different optimization goals. The performance of the proposed scheme is validated by comparing with conventional resource allocation schemes.